Effects of isoflavone supplementation on endometrial thickness, endometrial hyperplasia, and cancer in ovariectomized cats - Mona Negadmonfared; Reza Narenji Sani; Sahar Ghaffari Khaligh; Farzad Hayati (Veterinaria Italiana, 2022)
Ovariectomy is identified as a standard treatment in different European countries. Isoflavones, as nonsteroidal compounds in plants, are common constituents of soy and soy products. Some available cat diets contain different concentrations of soy products. This study aimed to examine the effects of isoflavone supplementation on endometrial hyperplasia and endometrial thickness in ovariectomized cats. Fifteen neutered adult cats were divided into control, estradiol, and isoflavone groups (five cats per group). Subcutaneous injection of estradiol (0.5 μg) in sesame oil (100 μL) was done for 30 days in estradiol-treated cats. Isoflavone-treated cats ingested a single oral tablet of soy extract for 30 days, while the controls received subcutaneous injections of the vehicle and oral placebo for 30 days. Histopathological findings of hematoxylin and eosin-stained sections revealed a significant difference between the estradiol group and other groups in terms of hyperplastic epithelium and simple hyperplasia. Thickness of myometrium was greater in the estradiol group compared to the isoflavone and control groups. Higher concentrations of estrogen can affect the endometrium and myometrium, while 30-day ingestion of isoflavone didn't have any uterine effect.